The Preferential Conditions for Land Acquisition as a Motivating Factor for Enlarging and Creating Farms in Poland - Klusek, Tomasz (Zeszyty Naukowe SGGW w Warszawie - Problemy Rolnictwa Światowego, 2015)
Transformations of the area structure of farms in Poland are determined by various factors among which the ability to acquire land on preferential terms is of critical importance. This thesis is supported, inter alia, by the analysis of sales realized in years 2010-2013 by the Agricultural Property Agency. They would not have been obtained, had it not been for farmer demand supported by the division of payments into installments or subsidizing interest payments on loans by the Agency for Restructuring and Modernization of Agriculture. The circumstances, scale and effects of this type of public aid as related to the creation of new agricultural holdings or enlargement of existing ones, are the subject of this study.